Agreement to prevent unregulated high seas fisheries in the Central Arctic Ocean (European Union, 2021)
This Agreement aims to prevent unregulated commercial fishing in the high seas portion (waters that are not under the jurisdiction of any country) of the Central Arctic Ocean by implementing precautionary conservation and management measures. It establishes a regional regulatory regime in line with the 1995 UN Fish Stocks Agreement and the Convention on the Law of the Sea. The Parties to this Agreement agree not to engage in commercial fishing activities in the high seas portion of the Central Arctic Ocean for an initial period of 16 years after the agreement enters into force. This period can be extended automatically every 5 years, unless one party objects. The Parties can only authorise vessels registered in their country to carry out commercial fishing if they follow: Internationally recognised conservation and management measures for the sustainable management of fish stocks adopted by one or more regional or subregional fisheries management organisation(s) or arrangement(s); or interim conservation and management measures that may be established by the Parties. The agreement is precautionary — until recently, ice has covered the high seas portion of the Central Arctic Ocean all year round, making fishing in those waters impossible. However, global warming has significantly reduced ice coverage, which may open up this area to fishing in the future. A review of the Agreement and of the scientific information obtained through the joint programme will take place at least every 2 years. Conservation and management measures for exploratory fishing in the area will be established within 3 years of the Agreement coming into force. There shall be compatibility between Parties' management and conservation measures efforts in line with the 1995 Straddling Fish Stocks Agreement.